Opgivelse af Kangerlussuaq - Lars Lund (Copenhagen Business School (CBS), Department of Economics, 2006)
The Greenland infrastructure for the airborne traffic uses Kangerlussuaq, Søndre Strømfjord, as hub. New scenarios may change that, and one possibility is the construction of a large airport at Nuuk with a 3000 m runway. The trunk line will then be between Copenhagen and Nuuk. In that case the village Kangerlussuaq will be abandoned. The paper analyses the size of the economic gain to Greenland of such a change. Using official statistics and information collected for the investigation a description is made of the employment structure and the income earned in the trades represented in Kangerlussuaq. It is then discussed to which extent people do tasks that will still be needed with the new structure and to which extent they will be set free to go into alternative production. The last possibility is regarded as a saving or as an increase in resources for Greenland, and the estimate is that this gain will amount to around 40 percent of the contribution to GDP in Kangerlussuaq. The saving is modified a little by the need of some new investments in Nuuk, mostly for housing.
hdl:10398/7507
Keywords: H00; 330